The stranger society the case of economic and social development in the tropics - Murphy, Peter (Budhi: a Journal of Ideas and Culture, 2015)
The economic and social prosperity of nations are usually attributed to functional requirements—such as honest government, effective transport and communication networks, health care and education—and development strategies such as investment in infrastructure. However, beyond a certain point peak economic and social success relies as much on human ingenuity as on capital investment. The article proposes that the world’s most prosperous societies have three recurring characteristics that foster such ingenuity: (1) they are all closely connected to trading portals, (2) they nourish paradoxical belief systems that underscore a proclivity for intellectual abstraction and pattern-based interaction, and (3) they are stranger societies that encourage high levels of interaction between unknown persons.